Density of the herbaceous layer and its relationship to light, pH and amount of litter in the Alberto Brenes Reserve, Costa Rica. (UNED Research Journal, 2016)
The biotic composition of many ecosystems is being altered quickly, so there is a growing need to understand ecological processes and maintain their biodiversity.  We measured the densities of the herbaceous layer of 30 miniplots (50 cm2) established in three transects (25m x 2m), at the Alberto Manuel Brenes Biological Reserve, San Ramon, Costa Rica. We found  that the factors influencing the density of herbaceous cover are pH and the amount of leaf litter.
Keywords: Herbaceous layer; pH; light; litter